Crystal structure of (E)-7-fluoro-2-(4-fluorobenzylidene)-3,4-dihydronaphthalen-1(2H)-one, C17H12F2O - Wei Pan-Pan; Meng Qing-Guo; Wang Bao-Gang; Hou Gui-Ge; Song Ya-Bin (Zeitschrift für Kristallographie - New Crystal Structures)
C17H12F2O, triclinic, P1¯ (no. 2), a = 7.9570(14) Å, b = 8.9872(19) Å, c = 9.3974(16) Å, α = 94.467(16)°, β = 96.737(14)°, γ = 103.162(16)°, V = 646.0(2) Å3, Z = 2, R gt(F) = 0.0417, wR ref(F 2) = 0.1112, T = 293 K.